First steps toward improving DoD STEM workforce diversity : response to the 2012 Department of Defense STEM Diversity Summit - Lim, Nelson; Haddad, Abigail; Butler, Dwayne M.; Giglio, Kate (Research report (Rand Corporation), 2013)
In FY 2011-2012, leaders from the Executive Branch and the Department of Defense (DoD) offered directives and guidance intended to increase diversity across all federal agencies. In response, the DoD Research and Engineering Enterprise and DoD's Office of Diversity Management and Equal Opportunity held a two-day summit in November 2012 on improving diversity within the science, technology, engineering, and mathematics (STEM) workforce. This report supports the efforts of the DoD STEM Diversity Summit by providing suggestions for future research, analysis, and action. The authors describe policies that discuss the federal government's values and priorities regarding diversity in the federal workforce; offer a closer look at current STEM demographics, including those of the DoD's STEM workforce; discuss current STEM-diversity outreach programs, highlighting the types of data that should be collected in the future; and offer recommendations for DoD leaders to consider as they move forward with their efforts to diversify the STEM workforce.